Computer aided chemical engineering (Excel/VBA) - Abd. Hamid, Mohd. Kamaruddin (Universiti Teknologi Malaysia, 2006)
This course introduces students to a solid introduction to programming concepts as well as numerical methods and statistical analysis. Students will receive instruction in the use of Excel spreadsheet basic and advanced features, VBA (Visual Basic for Applications) and macro programming as well as Excel's statistical functions. Students should master general programming concepts as well as gain an appreciation of formal problem solving methodology. Example problems draw from the chemical engineering field whereby the student learns to apply appropriate software or numerical methods. Problems will be taken from the areas of material and energy balances, thermodynamics, transport, kinetics, data fitting and analysis of experimental data and steady state and dynamic modelling.